A New Family of Stoneflies (Insecta: Plecoptera), Kathroperlidae, fam. n., with a Phylogenomic Analysis of the Paraperlinae (Plecoptera: Chloroperlidae). Issue 4 (2nd July 2021) - South, Eric J; Skinner, Rachel K; Edward DeWalt, R; Davis, Mark A; Johnson, Kevin P; Teslenko, Valentina A; Lee, Jonathan J; Malison, Rachel L; Hwang, Jeong Mi; Bae, Yeon Jae; Myers, Luke W
Abstract: Recent molecular analyses of transcriptome data from 94 species across 92 genera of North American Plecoptera identified the genus Kathroperla Banks, 1920 as sister group to Chloroperlidae + Perlodidae. Given that the genus Kathroperla has historically been included as a member of the family Chloroperlidae, this discovery indicated further investigation of the genus and the subfamily Paraperlinae was needed. Both transcriptome and genome sequencing datasets were generated from 32 species of the infraorder Systellognatha, including all described species of the Paraperlinae, to test the phylogenetic placement of these taxa. From these datasets, a large phylogenomic data matrix of 800 orthologous genes was produced, and multiple analyses were conducted, including both concatenated and coalescent analyses. Morphological comparisons were made among all Paraperlinae using light microscopy. All molecular results support a monophyletic Kathroperla, which is supported as sister taxon to the remaining Perloidea by five of six molecular analyses. Postocular head length is determined to be a distinct morphological character of this genus. Combined molecular and morphological evidence support the designation of Kathroperlidae, fam. n., as the seventeenth family of extant Plecoptera.